Description and molecular characterization of a new species of tarantula, Pamphobeteus verdolaga, from Colombia (Araneae: Mygalomorphae: Theraphosidae) (2016)
ABSTRACT: A new species of Pamphobeteus Pocock, 1901, is described from the Colombian Andes, Medellín, Antioquia. The biochemistry and molecular characteristics of the venom of this new species (previously identified as Pamphobeteus aff. nigricolor ) has been already described. A detailed taxonomic study, comparing this species with holotypes and additional material of Pamphobeteus species, allowed us to recognize it as new, and to describe it here as Pamphobeteus verdolaga sp. nov. The male of P. verdolaga sp. nov. is distinguished by the palpal bulb with broad embolus, poorly developed apical keel (A), prolateral inferior keel (PI) and prolateral accessory keel (PAc) present but poorly developed, and retrolateral keel (R) of similar length as A. Females are distinguished by the morphology of spermatheca with a wide base and very short oval seminal receptacles, which are curved toward the center. This is the thirteenth species described in Pamphobeteus and the sixth species reported from Colombia. The species description is complemented by a molecular characterization of a partial CO1 sequence.